Design and development of smart air-conditioning controller for achieving energy saving - Wee, Joshua Khui Ren (2024)
This project focuses on the design and development of a Smart Air Conditioning Controller (SACC) using a Fuzzy Logic (FL) algorithm as its decision-making engine. The primary goal of the SACC is to control air conditioning (AC) systems for energy savings without compromising user comfort. Three versions of the FL algorithm were developed, each with different input parameters, fuzzy sets, and rules, showing progressive improvement. The third version achieved 19.85% energy savings and maintained 63.21% more time in the thermal comfort zone, outperforming the baseline 24°C control scheme. The SACC also integrates Internet-of-Things (IoT) features, enabling remote monitoring and control, voice command for monitoring and control, and additional functionalities like automation, Overthe-Air (OTA) enabled, and Wi-Fi provisioning. Developed at a low cost, below RM 200, the SACC offers a plug-and-play solution, making it suitable for residential split-air conditioners. This project contributes to energy efficiency and decarbonization efforts by providing an affordable, userfriendly controller that balances energy savings with thermal comfort.